Comparison of Techniques for Obtaining Centric Relation Based on the Reproducibility of the Condylar Positions in Centric Relation—A Systematic Review - de Moraes Melo Neto, Clóvis Lamartine; dos Santos, Daniela Micheline; de Magalhães Bertoz, André Pinheiro; Moreno, André Luiz de Melo; Goiato, Marcelo Coelho (European Journal of Dentistry, 2021)
The objective of this systematic review was to compare centric relation (CR) techniques that belong to the same method of obtaining CR (guided, graphical, or physiological method), to verify which CR technique within each method of obtaining CR generates the greatest reproducibility of the condylar positions (or mandibular position) in CR. The PubMed, Cochrane Library, SciELO, Scopus, and Web of Science databases were searched for articles published up to May 5, 2021. The search terms were combinations of “dental centric relation” (MeSH), with each of the following terms (individually): “reproducibility of findings” (MeSH); “jaw relation record” (MeSH); “chin point”; “gothic arch”; “bimanual manipulation”; “swallowing” (MeSH); and “jig.” Inclusion criteria: clinical studies in English; individuals without temporomandibular dysfunction and with complete or almost complete dentition or complete edentulous; and comparison between CR techniques belonging to the same method of obtaining CR based on the reproducibility of condylar positions in CR. For each method of obtaining the CR, the following CR techniques were considered: guided method (chin point guidance and bimanual manipulation); graphic method (intraoral and extraoral gothic arch tracing); and physiologic method (swallowing and tongue retrusion along the palate). A total of 1692 articles were screened. After the inclusion and exclusion criteria were applied, six articles were included in this review. None of the included studies evaluated edentulous individuals. All included articles compared CR techniques of the guided method. Three articles concluded that the bimanual technique showed greater reproducibility of the condylar positions in CR than the chin point guidance technique, two articles showed equivalence between these techniques, and 1 article concluded that the chin point guidance technique showed greater reproducibility of the condylar positions in CR than the bimanual technique. Thus, in this systematic review, the bimanual technique was often superior (generated greater reproducibility of the CR) or at least equivalent to the chin point guidance technique. Therefore, for individuals with complete dentition and without temporomandibular disorders, the bimanual technique is more recommended.
Keywords: dental centric relation; reproducibility of findings; jaw relation record; chin point guidance; bimanual manipulation; gothic arch; swallowing